Division Electrosynthesis of Palladium Nanomaterials with Copper–Graphene as Sacrificial Templates and Its Application for Hydrazine Sensing. Issue 7 (16th June 2017) - He, Yaping; Han, Quan; Yang, Xiaohui; Zhang, Changhu; Zheng, Jianbin; Huo, Yanyan
Abstract : One‐pot electrodeposited copper‐graphene (Cu‐GE) nanocomposite acting as sacrificial template for the division electrosynthesis of palladium nanoparticles (PdNPs) on pyrolytic graphite electrode (PGE) was synthesized. The designed PdNPs‐GE nanocomposite was evaluated as a new material for highly sensitive determination of hydrazine (N2 H4 ). Scanning electron microscopy revealed that the PdNP‐GE‐modified PGE had uniform morphology. The results of energy‐dispersive X‐ray spectrograms confirmed the ingredients of the division electrosynthesis process. Electrochemical experiments were performed to characterize the sensing properties of PdNPs‐GE toward the electrocatalytic oxidation of N2 H4 at 0.20 V in sodium phosphate buffered saline (0.1 M pH 7.0). The sensor showed fast response (<3 s), high sensitivity [398 (1 × 10 −6 A) (1 × 10 −3 M) −1 ], and broad linearity in the range 2.5 × 10 −8 –2.7 × 10 −4 M with a relatively low detection limit of 1.0 × 10 −8 M (S/N = 3). Abstract : The fabricated N2 H4 sensor based on the division electrosynthesis of PdNPs on PGE, exhibited a variety of good electrochemical characteristics including fast response time, broad linearity, tow detection limit and high sensitivity. The microconstruction can give a relatively high specific surface area, evenly distributed mesoporosity and chemical stability, which are favorable for the effective immobilization of analyte molecule; GE was not only exhibited the signal amplification of nanosize materials, but also improved the electron transfer ability of this system.